Optimization of Carbon and Nitrogen Source on the Production of Pectinase Enzymes in Solid-state Fermentation by Cyberlindnera fabianii UNJCC Y-144 and Candida tropicalis UNJCC Y-148-149 Isolated from Lai Fruit - Dalia Sukmawati; Adisyahputra; Rifdah Hasanah; Shabrina Nida Al Husna; Nuniek Ina Ratnaningtyas; Adil Aksoy; Hesham Ali El-Enshasy (Journal of Pure and Applied Microbiology)
Yeasts are prevalent on the surfaces and within the pulp of ripening fruits, where they utilize available sugars and nutrients to thrive. This study focuses on the endemic Lai fruit (Durio sp.) from Kalimantan, Indonesia, which contains pectin, a key substrate for pectinolytic yeasts. The activity of these yeasts, particularly in producing pectinase enzymes, is influenced by the carbon and nitrogen resources present in the fruit. We aimed to evaluate the effects of varying carbon sources (glucose, sucrose, and pectin) and nitrogen sources (peptone, urea, and ammonium chloride) on the pectinase activity of yeasts isolated from Lai fruit. In our screening, five out of twenty yeast isolates demonstrated pectinase production, with three isolates UNJCC Y-144, UNJCC Y-148, and UNJCC Y-149 selected for further analysis. The initial screening revealed pectinolytic index values of 0.55 ± 0.07 mm, 0.45 ± 0.02 mm, and 0.49 ± 0.06 mm for UNJCC Y-144, UNJCC Y-148, and UNJCC Y-149, respectively. Molecular identification confirmed that UNJCC Y-144 is Cyberlindnera fabianii (100% homology), while UNJCC Y-148 and UNJCC Y-149 are Candida tropicalis (100% and 99.83% homology, respectively). Notably, Cyberlindnera fabianii UNJCC Y-144 exhibited the enzyme activity (EA) in a medium lacking pectin, ranging from 48.68 ± 2.84 to 32.05 ± 2.46 U/mL. These findings underscore the potential of utilizing local yeasts for biotechnological applications in enzyme production, particularly in the food industry, where pectinase plays a critical role in processing fruit and improving juice extraction efficiency.